Odysseus as a Target in the Odyssey and Aeschylus’ Fr. 179, 180 Radt (On the History of Greek Parody) - Ermolaeva, Elena (Hyperboreus, 2023)
This paper reviews the cases in which the heroic formulae of the Iliad appear in the non-heroic passages of the Odyssey, namely in the ﬁght scenes in the Iliad, which are repeated in the scenes where the suitors throw diﬀerent “missiles” at Odysseus (Od. 17. 462–465; 18. 396–398; 20. 299–302). While it would be incorrect to apply the notion of parody as a genre to the Odyssey itself, these examples show that epic heroic formulas appearing not in a strictly heroic context could provide material for a future Greek parody.